Gastric microbiota dysbiosis and Helicobacter pylori infection - Zhang, Ling; Zhao, Ming; Fu, Xiangsheng (Frontiers in Microbiology, 2023)
Helicobacter pylori (H. pylori) infection is one of the most common causes of gastric disease. The persistent increase in antibiotic resistance worldwide has made H. pylori eradication challenging for clinicians. The stomach is unsterile and characterized by a unique niche. Communication among microorganisms in the stomach results in diverse microbial fitness, population dynamics, and functional capacities, which may be positive, negative, or neutral. Here, we review gastric microecology, its imbalance, and gastric diseases. Moreover, we summarize the relationship between H. pylori and gastric microecology, including non-H. pylori bacteria, fungi, and viruses, and the possibility of facilitating H. pylori eradication by gastric microecology modulation, including probiotics, prebiotics, postbiotics, synbiotics, and microbiota transplant.